A literatura no cinema Oliveiriano - Sobral, Filomena Antunes (2018)
It is clear in the cinematography of the Portuguese emblematic director Manoel de Oliveira the influence of other arts, especially literature. Indeed, the literary adaptation impregnates the filmmaker’s interest in several filmic productions leading to works focusing on various themes, where prevails the female figure and Agustina Bessa-Luís texts. The involvement of the director in this context of intertextual dialogue goes back to his first fictional productions and remains throughout his extensive career. Studying the fictional universe of Oliveira is to rethink issues related to literary adaptation and its peculiarities. It is similarly to reflect on the role of adaptation in the Portuguese cinema and at the same time, to place the Portuguese filmmaker in the constellation of other paradigmatic filmmakers who established a dialogic relationship with written sources. In order to sustain the arguments, this reflection is anchored in literature and film studies and, at the same time, in the theory of adaptation. Highlighting the dialogical relationship between literature and film in the work of Manoel de Oliveira, this text seeks to establish a reflection on the literary adaptation and, in parallel, orientates the reader to the singularities of filmic transmutation emphasizing the various literary adaptations made by Oliveira that the Portuguese cinema has witnessed. The literature within Manoel de Oliveira’s films contributes to demonstrate the positive link that historically has connected these two forms of expression and offers an original exercise of rereading that accentuates the independence and the creative freedom of Manoel de Oliveira.